Analyzing major renewable energy sources and power stability in Taiwan by 2030. (February 2019) - Chuang, Ming-Tung; Chang, Shih-Yu; Hsiao, Ta-Chih; Lu, Yun-Ru; Yang, Tsung-Yeh
Abstract: The aim of this study is to assess the offshore wind and solar power and to determine whether the future power supply in Taiwan will be stable. The estimated annual offshore wind and solar power generation for 2030 are 11343 GWh and 11367 GWh, respectively. Based on these results, it appears that the annual power supply can easily help balance the total power demand. However, the power demand is high during the summer peak months, and power generation may be insufficient during peak summer hours by 2030. Specifically, in 2024, the peak hourly percent reserve margin (PRM) in summer will be negative (-0.9%). If the installation of offshore wind turbines and solar panels is delayed, then the problem of insufficiency will be even more severe. However, if the offshore wind and solar photovoltaic projects are completed on schedule, and the first, second, and third nuclear power plants (NPPs) extend their service to 2030, then the hourly PRM could reach 15% during the summer peak hours from 2025 to 2030 and 5–11% in the other years. Moreover, if the fourth NPP opens, then the estimated summer peak hourly PRM would increase by 6–7%. Graphical abstract: fx1 Highlights: Assessing the offshore wind and solar power in Taiwan by 2030. Analysis of the power stability in Taiwan by 2030. The hourly PRM is negative in 2024 even the installation of renewable energy is on schedule.